Vernacular graphic design: Interactive logos for tourism Terengganu - Muhammad Sophist, Ahmad; Imran, Abdullah; Mohd Hisham, Omar; Marzuki, Ibrahim; Suhaib Ahmed Mohammed, Alharahsheh (2021)
The tourism industry is one of the most important sectors for the economic development of a country around the world. Therefore, most countries use a variety of approaches including interactive graphic design to attract the attention of visitors traveling to their respective countries. In Malaysia, for example, most of the organizations involved in the tourism industry have strengthened their advertising towards interactive graphic design approach, especially the state tourism departments. One of the states in Malaysia that is actively developing tourism advertising and infrastructure is the state of Terengganu, which located on the east coast of peninsular Malaysia. In fact, the state of Terengganu has its own tourist attraction. There are many tourist attractions listed in the state. Among the organizations responsible for operating and promoting the tourism industry in the state is known as Terengganu Tourism. The Terengganu Tourism is an exemplary organization in the production of positive tourism advertisements, where a variety of creative and innovative tourism advertisements have been widely produced, and easily seen everywhere around the state. However, there are some matters related to the interactivity of the tourism ads that need to be improved, especially the identity of the logos. This study is conducted is to identify the main vernacular capacity found in the existing tourism logos, to analyse side-vernaculars for improvement to the existing tourism logos, and to recommend to Terengganu Tourism about the findings of new interactive graphic tourism logo design for their future tourism promotion use. This study was conducted based on qualitative research methods through time sampling observations and semi structured interviews. In addition, thematic analysis is also used to ensure that the theme of the study is coherent, consistent and distinctive. The findings of the study, which is the new interactive graphic tourism logo design, do have strong vernacular elements, such as diversity of culture, icon and heritage of the state of Terengganu. All efforts from Terengganu Tourism towards creative advertising, improvement in market segmentation, and innovative promotional campaigns at the national and international levels will be appreciated.